Evaluating the efficiency of one stop crisis centres in managing domestic violence cases - Siew, Ke Lin; Shirly Wong, Siew Ling; Chew, Keng Sheng; Vanitha, Kandasamy; Aida, Bustam; Muhammad Izzat, Abdul Hadi (Malaysian Medical Association, 2026)
Introduction: As domestic violence (DV) poses a critical threat to public health worldwide, this prompts the need for efficient and effective intervention. In Malaysia, although One Stop Crisis Centres (OSCCs) have been offering multisectoral services to DV victims for many decades, an evaluation of the efficiency of these centres has yet to be conducted. This study aimed to assess the efficiency and effectiveness of three Malaysian OSCCs using a two-stage Data Envelopment Analysis (DEA) approach.